2010
DOI: 10.1002/ptr.3163
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of panduratin A isolated from Kaempferia panduarata Roxb. on melanin biosynthesis

Abstract: Hyperpigmentation disorders are associated with abnormal accumulation of melanin pigments, thus melanin synthesis inhibitors have been of great interest as target molecules for cosmetic and medicinal purposes. The aim of this study was to investigate the in vitro inhibitory effect of panduratin A, isolated from Kaempferia pandurata Roxb., on melanogenesis and its related enzymes such as tyrosinase, tyrosinase related protein-1 (TRP-1) and tyrosinase related protein-2 (TRP-2) in melan-a murine melanocytes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…However, there is no further evidence regarding the reaction mechanism in these studies, and the inhibitors therefore cannot be classified into the sections described above. They include macelignan (Figure 10a) from Myristica fragrans [90], 2,3-epoxyjuanislamin (Figure 10b) from the leaves of Calea urticifolia [91], a black tea component theaflavin-3,3'-digallate (Figure 10c) [92], (2 Z ,8 Z )-matricaria acid methyl ester (Figure 10d) from Erigeron breviscapus [93], panduratin A (Figure 10e) from Kaempferia pandurata [94], sappanone A (Figure 10f) from Caesalpinia sappan [95], raspberry ketone (Figure 10g) from Rheum officinale [96], and manassantin A (Figure 10h) and B (Figure 10i) from Saururus chinensis [97]. …”
Section: Natural Melanogenesis Inhibitors Acting Through the Down-mentioning
confidence: 99%
“…However, there is no further evidence regarding the reaction mechanism in these studies, and the inhibitors therefore cannot be classified into the sections described above. They include macelignan (Figure 10a) from Myristica fragrans [90], 2,3-epoxyjuanislamin (Figure 10b) from the leaves of Calea urticifolia [91], a black tea component theaflavin-3,3'-digallate (Figure 10c) [92], (2 Z ,8 Z )-matricaria acid methyl ester (Figure 10d) from Erigeron breviscapus [93], panduratin A (Figure 10e) from Kaempferia pandurata [94], sappanone A (Figure 10f) from Caesalpinia sappan [95], raspberry ketone (Figure 10g) from Rheum officinale [96], and manassantin A (Figure 10h) and B (Figure 10i) from Saururus chinensis [97]. …”
Section: Natural Melanogenesis Inhibitors Acting Through the Down-mentioning
confidence: 99%
“…The rhizomes of this plant have been used for the treatment of peptic ulcer, as well as colic, oral diseases, urinary disorders, dysentery and inflammation [5]. Several studies have suggested this plant to be neuroprotective and to show anti-inflammatory, anti-mutagenic, anticancer, chemopreventive, anti-dermatophytic, anti-Helicobacter pylori and anti-dengue-2 virus NS3 protease activity [6]. This plant possesses both anti-oxidant, as well as anticancer properties which can help to cure cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated isopanduratin A and 4-hydroxypanduratin A to be promising compounds that could be useful for treating hyperpigmentation as skin-whitening agents. Panduratin A, isolated from Kaempferia panduarata , was found to inhibit melanin biosynthesis in melan-a murine melanocytes (Lee et al 2010 ). The IC 50 values of panduratin A for melanogenesis and tyrosinase were 9.6 μm and 8.2 μm, respectively, while those of arbutin as a positive control were 990 μm and 660 μm, respectively.…”
Section: Antityrosinase/skin Whitening Activitymentioning
confidence: 98%